Research Advances in Quantum Dynamics - Bracken, Paul (IntechOpen, 2016)
There continue at present many developments in the area of quantum mechanics and quantum dynamics in particular, of a very fundamental nature, all the way from implications for the foundations of physics to the influence of quantum mechanics on emerging technologies, such as the areas of quantum semiconductors and quantum computing, both of which are very important examples. It is hoped that the papers in this volume will be able to provide a much needed resource for researchers with regard to current fields of research in this dynamic area.